Characterization of aerosols above the Northern Adriatic Sea: Case studies of offshore and onshore wind conditions. (May 2016) - Piazzola, J.; Mihalopoulos, N.; Canepa, E.; Tedeschi, G.; Prati, P.; Zarmpas, P.; Bastianini, M.; Missamou, T.; Cavaleri, L.
Abstract: Aerosol particles in coastal areas result from a complex mixing between sea spray aerosols locally generated at the sea surface by the wind-waves interaction processes and a continental component resulting from natural and/or anthropogenic sources. This paper presents a physical and chemical analysis of the aerosol data acquired from May to September 2014 in the Adriatic Sea. Aerosol distributions were measured on the Acqua Alta platform located 15 km off the coast of Venice using two Particle Measuring System probes and a chemical characterization was made using an Ion Chromatography analysis (IC). Our aim is to study both the sea-spray contribution and the anthropogenic influence in the coastal aerosol of this Mediterranean region. To this end, we focus on a comparison between the present data and the aerosol size distributions measured south of the French Mediterranean coast. For air masses of marine origin transported by southern winds on the French coast and by the Sirocco in the Adriatic, we note a good agreement between the concentrations of super-micrometer aerosols measured in the two locations. This indicates a similar sea surface production of sea-spray aerosols formed by bubble bursting processes in the two locations. In contrast, the results show larger concentrations of submicron particles in the North-Western Mediterranean compared to the Adriatic, which result probably from a larger anthropogenic background for marine conditions. In contrast, for a coastal influence, the chemical analysis presented in the present paper seems to indicate a larger importance of the anthropogenic impact in the Northern Adriatic compared to the North-Western Mediterranean. Highlights: This paper is a contribution of the study of coastal aerosol properties over the Mediterranean. We study the sea-spray and the anthropogenic contributions in the aerosol concentrations measured in the Mediterranean coast. One of the objectives is to implement an accurate source term for the sea-spray aerosols in the aerosol transport model.